2020
DOI: 10.1097/hjh.0000000000002373
|View full text |Cite
|
Sign up to set email alerts
|

Vascular aging and its relationship with lifestyles and other risk factors in the general Spanish population: Early Vascular Ageing Study

Abstract: Objectives: To describe the prevalence of healthy vascular aging (HVA), normal vascular aging and early vascular aging (EVA) in a sample of Spanish population without cardiovascular disease. The relationship of vascular aging with lifestyle, cardiovascular risk factors, psychological and inflammatory risk factors is also analyzed. Methods: A total of 501 participants were recruited (49.70% men, aged 55.90 ± 14.24 years) by random sampling. Vascular agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…The EVA study was a descriptive transversal study (NCT02623894) and was intended to evaluate the association between different risk factors and vascular accelerated aging study. First results for the EVA study can be found in a previously published (Gomez-Sanchez et al, 2020).…”
Section: Designmentioning
confidence: 99%
“…The EVA study was a descriptive transversal study (NCT02623894) and was intended to evaluate the association between different risk factors and vascular accelerated aging study. First results for the EVA study can be found in a previously published (Gomez-Sanchez et al, 2020).…”
Section: Designmentioning
confidence: 99%
“…5 However, other cerebrovascular disease (CeVD) modifiable factors (such as hyperlipidemia, smoking, gender, and obesity) have yielded inconsistent results, especially hyperlipidemia. [6][7][8] Zhao et al 6 who examined 1133 Chinese individuals aged 50 to 90 years from a community showed that only low high-density lipoprotein cholesterol (HDL-C) was associated with high baPWV, whereas other lipid variables, such as total cholesterol (TC), triglyceride (TG) and low-density lipoprotein cholesterol (LDL-C), were not. Meanwhile, Yiming et al 8 conducted a cross-sectional study in Xinjiang and showed that just TGs were associated with baPWV.…”
mentioning
confidence: 99%
“…Multivariate logistic regression analyses were performed to investigate effect of HP infection on baPWV by adjusting for various well-known risk factors of peripheral arterial stiffness step by step, included the following well established variables by other studies: age, BMI, smoking, plasma levels of blood glucose, blood pressure, plasma lipids profiles as well as hsCRP, uric acid, and Hcy. 14 , 18 21 Otherwise, FBG can reflect the blood glucose level at the time of physical examination, while HbA1c can represent the average blood glucose level for the last 3 months, so when analysis the influence of HP infection on arterial stiffness, we corrected both FBG and HbA1c in the multivariate logistic regression analysis. Collinearity statistics were used to assess collinearity of the parameters used in the multivariate models.…”
Section: Discussionmentioning
confidence: 99%
“…In subjects with DM, arterial stiffness is closely associated with the progression of cardiovascular complications. 23 The pathology of arterial stiffness in subjects with DM is multifactorial and includes aging, obesity, smoking, 18 advanced glycation end products, 19 uncontrolled blood pressure, increased plasma levels of uric acid and hsCRP, 20 plasma lipid profiles and Hcy also related with progress of arterial stiffness in subjects with DM. 21 HP is gram-negative microaerophilic spiral bacterium, it has been suggested that the production of excessive amounts of proinflammatory factors and the cross-mimicry between HP and host antigens contribute to the pathologies of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%